2011
DOI: 10.1590/s0074-02762011000800006
|View full text |Cite
|
Sign up to set email alerts
|

Human polyomaviruses JC and BK in the urine of Brazilian children and adolescents vertically infected by HIV

Abstract: The aim of this study was to characterize the urinary excretion of the BK (BKV) and JC (JCV) human polyomaviruses in a cohort of human immunodeficiency virus (HIV)-infected children and adolescents. One hundred and fifty-six patients were enrolled: Group I included 116 HIV-infected children and adolescents [median age = 11.4 years (y); range 1-22 y]; Group II included 40 non-HIV-infected healthy controls (median age = 11.37 y; range 7-16 y). Single urine samples from both groups were screened for the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 16 publications
(20 reference statements)
0
12
1
4
Order By: Relevance
“…However a recent work published by MACHADO et al, 2011, found different rates of JCV and BKV urinary shedding in HIV+ children and non-infected children. In this study the BKV frequency was significantly higher in HIV infected patients in comparison of healthy subjects (54.3% vs. 12.5%) 33 . However the age of the participants of this study is very different from ours, it was not possible to compare the two groups.…”
Section: Discussionmentioning
confidence: 40%
“…However a recent work published by MACHADO et al, 2011, found different rates of JCV and BKV urinary shedding in HIV+ children and non-infected children. In this study the BKV frequency was significantly higher in HIV infected patients in comparison of healthy subjects (54.3% vs. 12.5%) 33 . However the age of the participants of this study is very different from ours, it was not possible to compare the two groups.…”
Section: Discussionmentioning
confidence: 40%
“…The results depicted here demonstrate that JCPyV and/or BKPyV DNA were more prevalent in renal transplant patients (72.8%) than in healthy individuals (53.4%). Significantly higher rates of polyomavirus infection among renal transplant patients have been previously shown by other authors, probably associated with the immunosuppressive therapy used in these patients [Machado et al, ; Rota et al, ].…”
Section: Discussionmentioning
confidence: 61%
“…Machado et al investigated the urinary excretion of BKPyV and JCPyV among HIV-1–infected children and adolescents and healthy controls and demonstrated a significantly higher BKPyV viruria in HIV-infected patients. No difference was observed for JCPyV excretion, however, and no association was found between CD4 + values and viral shedding ( 3 ). Jeffers et al assessed the salivary shedding of BKPyV on a cohort of healthy and HIV-immunosuppressed persons and found that BKPyV DNA levels in the saliva were significantly higher in HIV-infected patients.…”
mentioning
confidence: 99%